Intelligent human computer interaction : 9th International Conference, IHCI 2017, Evry, France, December 11-13, 2017, Proceedings /: 9th International Conference, IHCI 2017, Evry, France, December 11-13, 2017, Proceedings. (2017) - Unknown
No abstract available